The PIWI-interacting RNA CRAPIR alleviates myocardial ischemia‒reperfusion injury by reducing p53-mediated apoptosis via binding to SRSF1 - Yan Hong; Li Han; Yin Dao-hong; Zhang Zi-zhen; Zhang Qian-yun; Ren Zhong-yu; Hu Yu; Zheng Gui-yang; Liu Yu; Ma Wen-ya; Liu Yi-ning; Wang Xiu-xiu; et al. (Acta Pharmacologica Sinica, 2025)
Ischemia-reperfusion (I/R) injury refers to the secondary damage that occurs when blood flow is restored to heart tissues and organs following a period of prolonged ischemia. This damage is exacerbated primarily through mechanisms such as oxidative stress, inflammatory responses and apoptosis, all of which can severely impact patient prognosis. PIWI-interacting RNAs (piRNAs) represent a novel class of small noncoding RNAs that play pivotal roles in regulating gene expression and cellular functions. However, the precise role and underlying mechanisms of piRNAs in I/R injury remain poorly understood. In this study, we investigated the role and molecular mechanisms of a cardiac regeneration-associated PIWI-interacting RNA (CRAPIR), previously identified by our team, in I/R injury. An I/R injury model was established in adult male mice. The protein levels of cleaved caspase-3, Bax, Bcl2 and p53 were assessed using Western blotting, and cardiomyocyte apoptosis was detected via TUNEL staining. Our study revealed that, in I/R-damaged heart tissues and hypoxia‒reoxygenation (H/R)-induced cardiomyocyte models, CRAPIR was upregulated 24 h after I/R and H/R but was markedly downregulated at 72 h after I/R injury and 48 h after H/R injury. In the I/R mouse model, agomir-mediated overexpression of CRAPIR alleviated heart dysfunction and reduced cardiomyocyte apoptosis caused by I/R injury. Conversely, CRAPIR knockdown via an antagomir exacerbated I/R-induced cardiac dysfunction and increased the number of apoptotic cardiomyocytes. Mechanistically, CRAPIR interacts with serine/arginine-rich splicing factor 1 (SRSF1), triggering the upregulation of murine double minute 2 (MDM2) expression. The increased MDM2 promoted p53 ubiquitination, leading to reduced p53 levels. Furthermore, silencing SRSF1 or MDM2 attenuated the protective effect of CRAPIR against cardiomyocyte apoptosis following H/R injury. These findings suggest that CRAPIR serves as a critical regulator of I/R injury via the SRSF1/MDM2/p53 signaling pathway.